StochasticModels For Global Optimization Using Newton’sMethod - Siska Candra Ningsih; Yosza Dasril (Program Studi Statistika Unisba, 2005)
This paper will discuss the randomness and normality tests of the data collected by splittingthe interval [a,b] into several subintervals [xi,xi+1] (i = 0, ..., n-1) with x0 = a and xn = b for verifyingthat the optimization problem constitutes a Wiener process. Furthermore, the data can be used toevaluate the efficiency of probabilistic algorithm as proposed in this paper in determining the bestsubinterval to be explored by Newton’s method for searching the optimal point of global optimizationproblem.